Tribalism in American Politics: Are Partisans Guilty of Double-Standards? - Bernstein, Michael; Zambrotta, Nicholas S.; Martin, Scott D.; Micalizzi, Lauren (Journal of Open Inquiry in the Behavioral Sciences, 2025)
Political tribalism has increased dramatically in recent years. We explored partisan double-standards of Democratic and Republican voters across both hypothetical and real-world scenarios. In Study 1, participants rated the perceived legitimacy of election outcomes in response to hypothetical and ambiguous results from the 2020 presidential election. In Study 2 Part 1, college students and Amazon Turk volunteers rated their support of real-world presidential policies and actions. All policies/actions were attributed to Trump or Obama though they actually occurred under both presidents. In Study 2 Part 2, participants rated how bigoted various statements were; we manipulated who the utterances were attributed to (Trump v. Bill Clinton or Trump v. Martin Luther King [MLK]). Generally, Republican ratings were more favorable when statements were attributed to Trump vs. Democratic leaders while the opposite is true of Democrats. Crucially, these biases exist when evaluating identical information. Republicans and Democrats had a very small and very large tendency, respectively, to view statements as more bigoted under Trump vs. MLK. To the degree that this study can answer the question about which side is more guilty of double-standards, our results provide tentative evidence that this occurs under Democrats more than Republicans, though this overall difference may obscure important moderators. Our data provide evidence for tribal loyalty which may have significant social and political ramifications.